Analysing the Cost Efficiency: Evidence from Chinese Banks, 2012-2018 - Huang, Dongqi (2019)
China's banking industry has completed three rounds of reforms since 1978, and the latest round is now underway. However, due to the special society system in China, unbalanced regional development is a problem of long-standing. Although there are more and more researches focus on the cost efficiency of China’s banks in recent years, few of them examined the differences of economic regions and the influence of trans-regional operations on banking sectors. The purpose of this paper is to use the BC95 model of stochastic frontier analysis (SFA) method to measure the cost efficiency of China’s banking industry from 2012 to 2018. The model adopts the unbalanced panel data of the Chinese top 220 commercial banks. According to the empirical results measured by the BC95 model, the scores of cost efficiency are not identical in all 867 observations of 220 commercial banks in China and are not significantly affected by the macroeconomic factors including inflation, broad money growth and GDP growth. Besides, by comparing the cost efficiency scores of varied categories containing different years, types, regions and the impact of the regional expansion of commercial banks, it could be found that the cost efficiency scores of Chinese commercial banks show an upward trend during the study period. Besides, the cost efficiency scores of rural commercial banks and state-owned commercial banks are lower than that of foreign banks, city commercial banks and joint-stock commercial banks. Moreover, banks in central and eastern areas generally have higher efficiency scores than the west and northeast regions. And compared with local banks, trans-regional banks are more efficiency for the reason that trans-regional operations could reduce transaction and operating costs.